Implementasi Sistem Pemasaran Digital Marketing Pada Salah Satu UMKM “Geprek SS” Yang Ada Di Kelurahan Rungkut Tengah Surabaya - Nur Habibah Dwi Astuti; Novi Rahma Wati; Daisy Marthina Rosyanti; Sugeng Purwanto (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Digital marketing is an absolute tool for today's business people, because consumers are more inclined to carry out purchasing activities online, especially after the pandemic. On the other hand, optimizing the use of digital marketing is also an interesting topic in the business world. Considering that currently almost all business units use information technology to support their business operations, even MSMEs are no exception. But unfortunately, not all MSMEs understand the role of digital marketing in reaching potential markets.The use of digital marketing in its development is carried out as an effort to survive amidst the onslaught of increasingly complex business competition. One of the MSMEs that has not adapted to digital marketing is Geprek SS, which is in Rungkut Tengah Village, Surabaya. The purpose of this service activity is to provide assistance to Geprek SS business owners to utilize social media, create content in the form of videography and photography that can support product marketing. The method of implementing this activity is divided into three stages, namely: (1) Identification of problems which analyze what are the obstacles to the MSMEs Ayam Geprek SS and Needs Analysis; (2) Socialization and training to the owner of Ayam Geprek SS regarding the features available on social media and how to use them as digital marketing utilization; (3) Assisting the owner in implementing various explanations at the socialization and training stages so that they can use social media independently. The results of this activity are expected to be the MSMEs Ayam Geprek SS which has implemented digital marketing and is increasingly developing the contents or content in it so that it does not fade the branding of its products, and continues digital marketing and explores more features in social media.